Calculation and optimization of slope reinforcement at tunnel entrances—taking manyanpo tunnel as an example - Chen, Junzhi; Chen, Mingqing; Ren, Chunfang; Song, Jia (Frontiers in Earth Science, 2023)
Slope reinforcement is a common method to solve the problem of slope instability, and reasonable optimiza-tion of the corresponding support parameters is crucial for practical engineering. In this paper, the slope sup-port method of Manyanpo tunnel entrance section is taken as an example, and the theoretical calculation method is used to optimize the project cost. Combined with the orthogonal test, the sensitivity analysis of the influencing factors of the stability of the support system and the selection of the optimal parameter com-bination scheme are carried out. Then, based on flac3d software, the optimization scheme is compared with the original design scheme. The results show that the safety factor of the optimized scheme is increased from 1.32 to 1.43 compared with the actual project. The optimized support parameters have better control effect on the displacement of the slope, especially in the Z direction. The optimized parameters have better support effect. This study can provide reference for the optimization design of slope engineering support.